2000
DOI: 10.1083/jcb.148.4.791
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Raf-1 Disrupts Epithelial Tight Junctions via Downregulation of Occludin

Abstract: Occludin is an integral membrane protein of the epithelial cell tight junction (TJ). Its potential role in coordinating structural and functional events of TJ formation has been suggested recently. Using a rat salivary gland epithelial cell line (Pa-4) as a model system, we have demonstrated that occludin not only is a critical component of functional TJs but also controls the phenotypic changes associated with epithelium oncogenesis. Transfection of an oncogenic Raf-1 into Pa-4 cells resulted in a complete lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
161
2
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(177 citation statements)
references
References 41 publications
13
161
2
1
Order By: Relevance
“…3B). This finding is consistent with a requirement for MEK1 activity in the loss of ZO-1 from tight junctions and for the maintenance of the dispersed phenotype in epithelial cells expressing activated HaRas or Raf-1 (67,68). This finding also supports previous data indicating a requirement for PI3K activity in the breakdown of adherens junctions (55,57).…”
Section: Mek1-dependent Signals Synergize With Crkii To Promote the Lsupporting
confidence: 81%
“…3B). This finding is consistent with a requirement for MEK1 activity in the loss of ZO-1 from tight junctions and for the maintenance of the dispersed phenotype in epithelial cells expressing activated HaRas or Raf-1 (67,68). This finding also supports previous data indicating a requirement for PI3K activity in the breakdown of adherens junctions (55,57).…”
Section: Mek1-dependent Signals Synergize With Crkii To Promote the Lsupporting
confidence: 81%
“…The latter study reported leakiness, whereas the former did not, even though both reported evidence of cellular morphology and polarity changes as a result of the transformation. The finding that the downstream effector Raf-1 can also induce tight junction leakiness seems to support the contention by Chen et al (2000) that an activated Ras would in fact result in paracellular leak (Chen et al, 2000;Li and Mrsny, 2000). However, although Chen et al (2000) and Li and Mrsny (2000) reported Ras-and Raf-1-associated tight junction leak, it was not clear that the leak was on a molecular level, rather than a random loss of cells resulting in actual holes in the cell sheet.…”
Section: Resultscontrasting
confidence: 37%
“…The finding that the downstream effector Raf-1 can also induce tight junction leakiness seems to support the contention by Chen et al (2000) that an activated Ras would in fact result in paracellular leak (Chen et al, 2000;Li and Mrsny, 2000). However, although Chen et al (2000) and Li and Mrsny (2000) reported Ras-and Raf-1-associated tight junction leak, it was not clear that the leak was on a molecular level, rather than a random loss of cells resulting in actual holes in the cell sheet. Either diffusion through tight junctions or leak across multicellular holes in a cell sheet will both permit transepithelial flux of mannitol, PEG, or inulin at increased rates with similar first order kinetics.…”
Section: Resultscontrasting
confidence: 37%
“…Previous studies using a polarized rat parotid gland epithelial cell line have shown that the functional role of occludin in salivary epithelium is a critical component in TJ organization (Li and Mrsny 2000). Additionally, it may control phenotypic changes associated with epithelium oncogenesis (Li and Mrsny 2000).…”
Section: Discussionmentioning
confidence: 99%